Using a model to design, implement, and evaluate a training program for improving cultural competence among undergraduate nursing students: a mixed methods study - Jamileh Farokhzadian; Monirsadat Nematollahi; Nahid Dehghan Nayeri; Motahareh Faramarzpour (BMC, 2022)
Abstract Background Due to changing population, culturally diverse clients with different perceptions of illness and health are present in healthcare settings. Therefore, it is increasingly important for nursing students to have high levels of cultural competence in order to meet diverse client needs. A training program is essential to enhance students' cultural competence. This study aimed to design, implement, and evaluate a cultural care-training program to improve cultural competence of undergraduate nursing students. Methods This exploratory mixed methods study used six steps proposed in the Talbot and Verrinder model to design a training program. In the first step, a conventional qualitative study was conducted and 18 participants were interviewed using purposive sampling. In the second and third steps, literature review and the classic Delphi technique were used for initiation and finalization of the program. The fourth, fifth, and sixth steps were completed by implementing, monitoring, and evaluating the cultural care program (five two-hour sessions) among 73 nursing students using a quasi-experimental design. Finally, effectiveness of program was evaluated through the cultural care inventory before and 1 month after the program. Data were analyzed via SPSS25, independent samples t- test, paired t- test, chi-square test, analysis of covariance, and multivariate linear regression tests. Results A systematic model was used to identify key elements of a cultural care program, including main topics, educational objectives and contents, assignments and activities for students, teaching and evaluation methods. The curricular objectives and educational contents were implemented in five sessions to produce measurable results. The quantitative step showed that nursing students' cultural competence in the intervention group (184.37 ± 22.43) improved significantly compared with the control group (153.19 ± 20.14) (t = 6.24, p = 0.001) after intervention. Conclusion A cultural care training program can be designed by the model applied in this study in order to improve cultural competence of nursing students. This training program will be effective if students' learning needs, appropriate assignments, and acceptable teaching methods are addressed. Therefore, nurse educators can design comprehensive training programs to improve nursing students' cultural competence in different cultures and contexts. This training program is highly efficient because it is applicable in many disciplines of nursing education.